An exploration of organizational characteristics and training adoption in Irish community drug treatment services - Kelly, Peter (My University, 2022)
Background: Changes in patterns of drug use and population needs necessitate the adoption of new technologies. Despite high failure rates in adopting new technologies acquired in training, little is known about the process which can support successful change. This study explores the impact that staff and service characteristics have on the process of training adoption in Irish opiate substitution therapy services, with a specific focus on the concept of organizational readiness to change. Methods: A cross-sectional survey was conducted on a convenience sample of 132 staff members across 12 services in Ireland. The relationship between staff demographics, their perceptions of organizational readiness to change, burnout and a 4-stage process of training adoption were considered. Results: Discipline, job tenure and educational levels are important predictors of engagement in the adoption process. Staff in services with higher institutional needs, greater pressures for change and poorer resources were less likely to be exposed to, or adopt training. Having lower levels of stress and more influence with peers was associated with better adoption of training. Conclusions: Planners and service managers need to carefully consider the composition or dynamics of services when initiating change. Organizational readiness to change and staff characteristics as measured by instruments used in this study are important determinants of the process of innovation or training adoption and provide a good basis for developing further understanding of how treatment services work. This paper expands on results from previous studies conducted in the US, to a European context.
ACCEPTED
In press
Keywords: Innovation adoption; Substance use; Training; Organizational readiness to change; Dissemination; Inclusive Society; Education and training; IMPLEMENTATION SCIENCE; Organisational behaviour; SUBSTANCE MISUSE; Mental Health/Psychosocial disability; Health; Policy; Social exclusion